2002
DOI: 10.1149/1.1479154
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Effect on Densification and Thermal Expansion Compatibility for La[sub 0.8]Sr[sub 0.2]Cr[sub 0.9]Ti[sub 0.1]O[sub 3]-Based SOFC Interconnect with B-Site Doping

Abstract: The air-sintering characteristics and thermal expansion behaviors in the La 1Ϫx Sr x Cr 0.9 Ti 0.1Ϫy Co y O 3 ͑0.15 р x р 0.20 and 0 р y р 0.02͒ and La 0.8 Sr 0.2 Cr 1Ϫx Ti 0.1 M x O 3 ͑M ϭ V and Ni; 0 р x р 0.05͒ systems have been investigated as an interconnect material in high-temperature solid oxide fuel cells ͑SOFCs͒. With the exception of La 0.8 Sr 0.2 Cr 0.85 Ti 0.1 V 0.05 O 3 , all samples showed a single perovskite phase with the hexagonal symmetry. La 0.8 Sr 0.2 Cr 0.85 Ti 0.1 V 0.05 O 3 contained a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Interconnecting materials are mainly alloys (Ni-Cr) with high temperature resistance and doped perovskite-type composite oxides (La1-xCaxCrO3 or La0.8Sr0.2Cr0.9Ti0.1O3) [130,131]. To avoid the shortcomings of composite oxides, i.e.…”
Section: Solid Oxide Fuel Cellsmentioning
confidence: 99%
“…Interconnecting materials are mainly alloys (Ni-Cr) with high temperature resistance and doped perovskite-type composite oxides (La1-xCaxCrO3 or La0.8Sr0.2Cr0.9Ti0.1O3) [130,131]. To avoid the shortcomings of composite oxides, i.e.…”
Section: Solid Oxide Fuel Cellsmentioning
confidence: 99%
“…Similarly, small levels of V, Co, Ni doping were shown to enhance the air sintering characteristics of La 0.8 Sr 0.2 Cr 0.9 Ti 0.1 O 3 , with V doping giving the greatest effect. 142 Ovenstone et al have shown that a combination of hydrothermal processing followed by high temperature sintering resulted in dense pellets of La 0.7 Ca 0.3 CrO 3 and La 0.84 -Sr 0.16 CrO 3 at lower temperatures than by conventional synthesis routes. 143 Further work on supported mixed gas SOFCs was presented by Raz et al 144 In these systems the anode and cathode are both exposed to the same mixture of gases, and the potential is generated due to the differences in catalytic activities between anode and cathode.…”
Section: Oxide Ion Conductors/solid Oxide Fuel Cellsmentioning
confidence: 99%
“…The substitution of either on A or B sites in the ABO3 perovskite materials is currently used to improve electrical properties and sintering behavior. Although thermal-electrical properties of the alkaline-earth-doped lanthanum chromites is good, its sintering behavior is very bad in air due to the high vapor pressure of the chromium oxide [1][2][3][4][5]. Therefore, several attempts to overcome this bad weak point have been performed to densify lanthanum chromites and to improve the sintering behavior [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%